Leakage Performance of the GM + CCL Liner System for the MSW Landfill - Fan Jingjing (The Scientific World Journal)
The contaminants in the landfill leachate press pose a grave threat to environment of the soil and the groundwater beneath the landfill. Despite there being strict requirements in relevant provisions of both domestic and foreign countries for the design of the bottom liner system. Pollution of the soil and the groundwater still took place in a number of landfills because of the leakage. To investigate the leakage rate of the liner systems, the minimum design requirements of the liner systems are summarized according to the provisions of four countries, including China, USA, Germany, and Japan. Comparative analyses using one-dimensional transport model are conducted to study the leakage performance of these liner systems composed of geomembrance (GM) and compacted clay layer (CCL) meeting the relevant minimum design requirements. Then parametric analyses are conducted to study the effects of the hydraulic head, the thickness of GM, the hydraulic conductivity of CCL, and so forth on the leakage performance of the liner system. It is concluded that the liner system designed according to the minimum design requirements of Germany provide the best antileakage performance, while that of Japan performs the lowest. The key parameters affecting the failure time of the liner system are summarized. Finally, some suggestions for the design of the liner systems are made according to the analyses.